2020
DOI: 10.2196/19723
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Low-Cost Portable 3D Virtual Reality Simulator for Psychomotor Skill Training in Minimally Invasive Surgery: Task Metrics and Score Validity

Abstract: Background The high cost and low availability of virtual reality simulators in surgical specialty training programs in low- and middle-income countries make it necessary to develop and obtain sources of validity for new models of low-cost portable simulators that enable ubiquitous learning of psychomotor skills in minimally invasive surgery. Objective The aim of this study was to obtain validity evidence for relationships to other variables, internal st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 112 publications
2
11
0
Order By: Relevance
“…From the 92 published studies, VS was reported to be applied in the educational practice involving undergraduate medical students across 25 countries including the United States [26 studies ( 15 40 )], the United Kingdom [9 studies ( 41 49 )], Germany [7 studies ( 50 – 56 )], China [6 studies ( 10 , 57 61 )], Denmark [6 studies ( 62 – 67 )], France [4 studies ( 68 71 )], Japan [4 studies ( 72 75 )], Sweden [3 studies ( 76 78 )], Canada [3 studies ( 79 – 81 )], Netherlands [3 studies ( 82 84 )], Spain [3 studies ( 85 87 )], Australia [2 studies ( 88 , 89 )], Singapore [2 studies ( 90 , 91 )], Korea [2 studies ( 92 , 93 )], Finland [1 study ( 94 )], Italy [1 study ( 95 )], Ireland [1 study ( 96 )], Colombia [1 study ( 97 )], Pakistan [1 study ( 98 )], Thailand [1 study ( 99 )], Iran [1 study ( 100 )], Poland [1 study ( 101 )], Mexico [1 study ( 102 )], Norway [1 study ( 103 )], Saudi Arabia [1 study ( 104 )], and Switzerland [1 study ( 105 )]. The distribution of included studies among different continents was shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…From the 92 published studies, VS was reported to be applied in the educational practice involving undergraduate medical students across 25 countries including the United States [26 studies ( 15 40 )], the United Kingdom [9 studies ( 41 49 )], Germany [7 studies ( 50 – 56 )], China [6 studies ( 10 , 57 61 )], Denmark [6 studies ( 62 – 67 )], France [4 studies ( 68 71 )], Japan [4 studies ( 72 75 )], Sweden [3 studies ( 76 78 )], Canada [3 studies ( 79 – 81 )], Netherlands [3 studies ( 82 84 )], Spain [3 studies ( 85 87 )], Australia [2 studies ( 88 , 89 )], Singapore [2 studies ( 90 , 91 )], Korea [2 studies ( 92 , 93 )], Finland [1 study ( 94 )], Italy [1 study ( 95 )], Ireland [1 study ( 96 )], Colombia [1 study ( 97 )], Pakistan [1 study ( 98 )], Thailand [1 study ( 99 )], Iran [1 study ( 100 )], Poland [1 study ( 101 )], Mexico [1 study ( 102 )], Norway [1 study ( 103 )], Saudi Arabia [1 study ( 104 )], and Switzerland [1 study ( 105 )]. The distribution of included studies among different continents was shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…We are aware that the rating for the face evaluation is subjective and influenced by several factors, such as an enthusiastic presentation of the simulator and the motivation of participants to improve performance, consistency of the performance, and the decrease in the number of errors. Nevertheless, the rating for training capacity and realism presented in other studies for different simulator systems are varying in the convincing [ 11 , 12 ], recently several 3D portable simulators, although not being able to demonstrate differences between the performance scores between experts and surgical novices, are still showing good consistency and reliability [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The second is constructive evaluation, which demonstrates the improvement of the participants in the training session and the ability of the designed task to distinguish the experienced from the inexperienced surgeon based on the performance score. The third step is predictive evaluation, which demonstrates the beneficiary effect of training four weeks afterward on the practice of surgeons addressed with five questions [ 8 , 9 ] ( Appendix A ).…”
Section: Methodsmentioning
confidence: 99%
“…This increases the teaching realism and meaningful learning thanks to a full interaction with neuroanatomical virtual models. According to this, several authors have analyzed the use of VR and LMC in anatomy teaching and training of surgical and healthcare procedures ( Ferreira dos Santos et al, 2016 ; Yeo et al, 2018 ; Kyaw et al, 2019 ; Alvarez-Lopez et al, 2020 ), or engineering training among others ( Häfner et al, 2013 ). After using LCM, students reported that it was a useful, easy-to-use and effective device for anatomy learning, highlighting its precision for hand and finger recognition ( Nainggolan et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%